Drug-related problems and potential contributing factors in the management of deep vein thrombosis. Issue 1 (December 2016) - Daba, Fekede; Tadesse, Fisihatsion; Engidawork, Ephrem
Abstract Background Patients receiving anticoagulant drugs must be carefully screened for drug-related problems, as such medications, including warfarin have narrow therapeutic ranges and a high potential for complications. Thus, this study was designed to assess drug-related problems in the management of patients with deep vein thrombosis at Tikur Anbessa Specialized Hospital. Methods A cross-sectional descriptive study involving retrospective chart review of adult patients with deep vein thrombosis was conducted from patients who visited the hospital from July 2012 to June 2013, using structured data collection format and this was complemented by key informant interview. Results The study included 91 patients with venous thromboembolism. Fifty three (58.2 %) were females. Mean age was 38.6 (±13.76) years and more than 2/3 were below the age of 44 years. About 54 % of them presented with concurrent medical conditions and most commonly with cancer. Adjustment of warfarin dose up or down was done in increments of 16 to 100 % for recent subtherapeutic International Normalized Ratios, 16 to 50 % for therapeutic and 11 to 66 % for overtherapeutic International Normalized Ratios, with the mean of 36.5 (±18.03) based on the cumulative weekly dose of warfarin. There was significant linear relationship between percentage of dose change and consequent International Normalized Ratio values (R2  = 0.419;p  = 0.000). Accordingly, more than 51 % of them presented with nontherapeutic International Normalized Ratio ranges following dose adjustment. Conclusions The most prevalent anticoagulation drug-related problems were subtherapeutic doses, overtherapeutic doses and potential drug interactions. Institutional validated decision support tools for dosing decisions during maintenance anticoagulation therapy should be developed and used accordingly in order to prevent recurrent and hemorrhagic complications and to improve clinical outcomes.